From state dissociation to status dissociatus. (August 2016) - Antelmi, Elena; Ferri, Raffaele; Iranzo, Alex; Arnulf, Isabelle; Dauvilliers, Yves; Bhatia, Kailash P.; Liguori, Rocco; Schenck, Carlos H.; Plazzi, Giuseppe
Summary: The states of being are conventionally defined by the simultaneous occurrence of behavioral, neurophysiological and autonomic descriptors. State dissociation disorders are due to the intrusion of features typical of a different state into an ongoing state. Disorders related to these conditions are classified according to the ongoing main state and comprise: 1) Dissociation from prevailing wakefulness as seen in hypnagogic or hypnopompic hallucinations, automatic behaviors, sleep drunkenness, cataplexy and sleep paralysis 2) Dissociation from rapid eye movement (REM) sleep as seen in REM sleep behavior disorder and lucid dreaming and 3) Dissociation from NREM sleep as seen in the disorders of arousal. The extreme expression of states dissociation is characterized by the asynchronous occurrence of the various components of the different states that prevents the recognition of any state of being. This condition has been named status dissociatus . According to the underlying disorders/diseases and to their severity, among status dissociatus we may recognize disorders in which such an extreme dissociation occurs only at night time or intermittently (i.e., autoimmune encephalopathies, narcolepsy type 1 and IgLON5 parasomnia), and others in which it occurs nearly continuously with complete loss of any conventionally defined state of being, and of the circadian pattern ( agrypnia excitata ). Here, we render a comprehensive review of all diseases/disorders associated with state dissociation and status dissociatus and propose a critical classification of this complex scenario.